2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6091894
|View full text |Cite
|
Sign up to set email alerts
|

In vivo characterization of ultrasonic transducers for the detection of airway occlusion in Sleep Disordered Breathing

Abstract: Obstructive Sleep Apnea/Hypopnea Syndrome (OSAHS) is the most common form of Sleep Disordered Breathing (SDB) and it is estimated to affect approximately 15% of US adult population. Various methods have been proposed for the development of inexpensive screening methods to detect SDB to reduce the need for costly nocturnal polysomnography (NPSG). In this paper, a description of the ultrasonic transducer design and characterization is presented, followed by the results of a full night sleep study. The findings s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The design, fabrication, and in vivo characterization of the sensor arrays used in this study were reported in [8]. The design of the transducers followed an optimization process.…”
Section: A Ultrasonic Sensor Array Design and Fabricationmentioning
confidence: 99%
See 4 more Smart Citations
“…The design, fabrication, and in vivo characterization of the sensor arrays used in this study were reported in [8]. The design of the transducers followed an optimization process.…”
Section: A Ultrasonic Sensor Array Design and Fabricationmentioning
confidence: 99%
“…The smaller this angle is, the higher the transducer's directivity [9]. The design considerations for the receiver transducers are similar to those for the transmitter [8]. However, in order to achieve maximum reception, these transducers need to be designed with a wider beam width to allow for normal and oblique incidence of the received ultrasonic waveform, to account for the curvature of the neck.…”
Section: A Ultrasonic Sensor Array Design and Fabricationmentioning
confidence: 99%
See 3 more Smart Citations